1985
DOI: 10.1577/1548-8640(1985)47<135:aaffc>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Allowable Ammonia for Fish Culture

Abstract: A review of the published literature on effects of ammonia on fish indicates that un-ionized ammonia alone is probably not the cause of gill hyperplasia, indicative of, or previously attributed to, chronic ammonia poisoning. The maximum safe concentration of un-ionized ammonia is unknown, but in many cases it is not close to the 0.0125 mg/L value commonly accepted by fish culturists.There is confusion concerning the sublethal, chronic effects of ammonia exposure on fish. In this review I attempt to point out i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(124 citation statements)
references
References 3 publications
7
113
1
3
Order By: Relevance
“…The acute and chronic toxicities of ammonia have been extensively reviewed for freshwater fishes (Wang & Walsh, 2000;Biswas et al, 2006;Reddy-Lopata et al, 2006). High levels of ammonia cause stress and produce harmful physiological response such as osmoregulatory disturb, kidneys and branchial epithelium damages (Meade, 1989;Soderberg, 1994), retarded growth, inefficient immune response (Cheng et al, 2004;Pinto et al, 2007) and reduced survival (Jobling, 1994). The findings in the current experiments indicated 100% survival of the fish in 96-h exposure to the control and 0.9-mg/L of total ammonia, while 98, 88, 85, 62, 30 and 25% of the fish survived to 1.4, 8.5, 13.1 18.6, 23.7 and 35.6 mg/L of total ammonia (or 0, 0.022 0.032, 0.19, 0.23, 0.31, 0.44 and 0.85 mg/L NH 3 ) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The acute and chronic toxicities of ammonia have been extensively reviewed for freshwater fishes (Wang & Walsh, 2000;Biswas et al, 2006;Reddy-Lopata et al, 2006). High levels of ammonia cause stress and produce harmful physiological response such as osmoregulatory disturb, kidneys and branchial epithelium damages (Meade, 1989;Soderberg, 1994), retarded growth, inefficient immune response (Cheng et al, 2004;Pinto et al, 2007) and reduced survival (Jobling, 1994). The findings in the current experiments indicated 100% survival of the fish in 96-h exposure to the control and 0.9-mg/L of total ammonia, while 98, 88, 85, 62, 30 and 25% of the fish survived to 1.4, 8.5, 13.1 18.6, 23.7 and 35.6 mg/L of total ammonia (or 0, 0.022 0.032, 0.19, 0.23, 0.31, 0.44 and 0.85 mg/L NH 3 ) respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The values of nitrite-nitrogen ranging from 0.01 to 0.11 mg l -1 and nitrate-nitrogen ranging from 0.09 -0.66 mg l -1 in different treatments were recorded which were within safe levels (Meade, 1985;Banerjee and Lal, 1990;Lyssenko and Wheaton, 2006). Concentrations of orthophosphates were significantly lower in T1 in comparison with T2 and T3 (p<0.05), but the variations were insignificant between T2 and T3 (p>0.05).…”
Section: Water Quality Parametersmentioning
confidence: 68%
“…Ammonia is toxic to fish and is considered to be a major factor limiting fish growth in intensive culture systems (Thurston et al, 1983;Cai and Summerfelt, 1992;Forsberg and Summerfelt, 1992;Leung et al, 1999). It is suggested by several researchers that the TAN values should be less than 1 mg l -1 for good growth of all aquaculture species (Meade, 1985;Jena and Das, 2006). During the present study, TAN values were found to be more than 1 mg l -1 in the treatments T2 and T3 in the months of October, November and last week of February, March and April.…”
Section: Water Quality Parametersmentioning
confidence: 99%
“…Essa conversão promove o aumento da toxicidade no meio, e embora a concentração do nitrogênio amoniacal seja reduzido ao longo do tempo, seu efeito tóxico aumenta. Estudos realizados por Meade [18] mostram que a forma não iônica da amônia é 300-400 vezes mais tóxica do que a sua forma iônica .…”
Section: Figuraunclassified